MAN AND EDUCATION – A LIFE LONG JOURNEY - Dr. Chittibabu Putcha and Dr. Pallavi Priyadarshini (International journal of economic perspectives, 2022)
Education is the production of desirable changes in human behavior. These changes are brought out in the social and cultural aspects of human life. This article is focus on various factors affection learning. Learning process, Education and society